PENGARUH KEADILAN KOMPENSASI, KEBIJAKAN ROTASI KARYAWAN DAN KOMITMEN AFEKTIF PADA PERILAKU RETALIASI PNS KANTOR “X” DI YOGYAKARTA - Majang Palupi (Fakultas Bisnis UKDW, 2013)
This study showed that retaliation behavior is an important concept in organizational behavior domain. However organizational justice perception and affective commitment are important antecedences to explain retaliation phenomena at workplace. Based on social exhange theory, financial compensation and rotation policy are important purposes of most employees related to their reason to affiliate with an organization. This research has done in an Indonesian’s Government institution where the researcher gathered 77 subjects of fulltime employees. Add up the results supported hypothesis partially. In general, the conclusion of this study explained that the distributive justice of rotation policy and affective commitment have strong prediction to employee’s retaliation in workplace. But distributive justice of financial compensation didn’t support hypotheses. The context had explained possibility why the distributive justice of financial compensation didn’t support hypotheses. Keywords: retaliation, distributive justice of financial compensation, distributive justice of employee’s rotation policy and affective commitment